Research needs to become popular (PUBMET, 2023)
Open access (sometimes referred to as Public Access in the US) to academic publications and FAIR research data increases public scrutiny in research, but these two directions of travel are not enough to produce a profound change for the society and the research culture itself.Let’s be frank: Research is still an elitist activity, defined by a hermetic culture. Some call it “The Ivory Tower”. Ordinary people know little about research practices and, with a few exceptions, people are not used to contributing to and consuming research. One effect of this elitist state is that Research became a small-community, well-oiled machine based on public grants and proxy-style assessments. Meanwhile, 70% of Research remains nonreplicable, and the research community continues to struggle to sink this number. This is bad. For this reason and with respect to what Research represents (hopes, needs, healthy progress and, more recently, reparations) both Research and Society need deeper scrutiny tools to understand and encourage participation in the process of creating knowledge.At the same time, we remain slow in identifying flawed research. Lives, hopes and important resources are lost that way. Too many researchers are complacent about the system. Left alone, Peer Review is not capable enough to distill good from bad research. The lack of public scrutiny into how knowledge is produced remains a cause for sideslips in research.This presentation challenges the current understanding that Research should remain an esoteric sector of our society. In a “message-from-the-future” manner, this presentation promotes the idea of open and participatory research and invites the audience to coalesce to make possible a deeper and healthier scrutiny of research activities.Starting with a declaration in Rome (2014) and continuing with theoretical frameworks, monitoring programmes, and practitioners’ networks, the EU triggered a series of actions around what is called Responsible Research and Innovation (RRI). It constitutes an important building block for “aligning research and innovation to the values, needs and expectations of society”. While progress has been slow, it has the potential to improve Research and the relationship between science and society. Recognising the work surrounding RRI, this presentation invites the audience to travel beyond the RRI horizon: to imagine a world in which Society feels welcomed and invited into the researchers’ world.Through a comparison with the evolution of gastronomy, this presentation provokes the audience to imagine how the world could be changed by turning research into a popular culture, like literature, music, travel, and gastronomy turned out to be. Cultures become popular when ideas, customs, and behaviours are embraced by large parts of the population. They have the potential to become part of community identity when they are strong enough to mark with their characteristics the past, the present and the future. Literature, Gastronomy, Music, and others did it. What kind of world would we get if Research achieved the same? Setting this question in a thoughtful manner is the main novelty of this presentation.Another possible novelty could be the presentation style which will be unusual, with the presenter speaking from the year 2065 to an audience from 2025.In summary, the role of this presentation is to inspire the audience. It promotes the idea that research deserves to be a popular culture and gives a vision about a possible future for Research.
Keywords: research integrity; open science; citizen science; third mission; research ethics; popular cultures